The Effectiveness of the Educational Program Through Audio Visual Media about Hand Hygiene and Diarrhea on the Knowledge of Students in Matungkas State Elementary School, North Minahasa Regency Indonesia - Sarimin, Dorce Sisfiani; Pasambo, Yourisna; Tangkudung, Yesika; Ponidjan, Taty S.; Ransun, Djoni (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Background:School-age children have a habit of paying less attention to the need to wash their hands in daily life, especially when in the school environment. They usually directly eat the food they buy around the school without washing their hands first. The behavior is certainly influential and can trigger the occurrence of diarrhea. Learning using interesting methods can increase knowledge and make it easier for children to understand hand hygiene and diarrhea.Objective: To find out the effectiveness of educational programs through audio visual media about hand hygiene and diarrhea on the knowledge of Matungkas State Elementary School students, North Minahasa Regency.Method: Using an approachQuasi Experimental with non equivalent control group design. The research subjects were 86 respondents, the sampling method was by probability sampling who fit into the inclusion criteria. The measuring instrument used is a knowledge questionnaire hand hygiene and diarrhea. Results of analysis with testsMann Whitney shows that there is a difference in value posttest knowledge of both groups with a P-valueValueequal to 0.000 means P-Value <0.05. Conclusion:Health education in the experimental group which used audio-visual media was more effective than the control group which was given health education through lectures using leaflets, but both groups experienced an increase in knowledge. In conclusion, educational programs through audio-visual media are effective in increasing knowledge about hand hygiene and diarrhea in students at SD Negeri Matungkas, North Minahasa Regency